PENTINGNYA BODY IMAGE POSITIF PADA MASA ANAK-ANAK AWAL - amalia, lia (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2024)
Body image disturbance has been listed as a diagnostic feature of several psychopathological conditions. As body image concerns appear in children as young as 2-5 years old, it was hypothesized to be an important risk factor for the development of psychopathology, such as Eating Disorders (ED) in adolescence and depression in adulthood. Several research findings support the hypothesis that body image dissatisfaction occurs much in advance of the onset of puberty and can be observed in children as young as 5 to 7 years old that’s why this study is very important. The purpose of the present paper is to identify substantial gaps in Bahasa literature concerning body image in children. The focus is on three major issues: (1) the definition of body image, (2) negative and positive body image, and (3) the development body image in children. Addressing these and related questions will aid in the development of treatment and prevention programs to build positive body image in children.